Gas chromatography-mass spectrometry profiling, bioactive compounds and cytotoxicity of edible-cricket extracts as inhibitors for alpha-glucosidase, alpha-amylase, tyrosinase, and acetylcholinesterase - Masoongnoen, Jintana; Sansenya, Sompong; Wechakorn, Kanokorn (Agriculture and Natural Resources, 2023)
Importance of the work: In Thailand, consumption is increasing of edible crickets as a future prospective food, due to their various nutrient components and high level of proteins. Objectives: The crude extracts of several edible cricket insect species were investigated for their levels of enzyme inhibition activity regarding diabetes, Alzheimer’s disease and melanogenesis. Materials & Methods: Several bioactive compounds, including alkaloids, saponins, steroids, triterpenoids, tannins, phenolics, and flavonoids, were investigated in the cricket extracts using the solvent extraction method and subsequently analyzed using gas chromatography-mass spectrometry (GC-MS) profiling and their inhibitory levels regarding -glucosidase, -amylase, tyrosinase and acetylcholinesterase. Results: The total phenolic and flavonoids in the methanol extracts had greater inhibition levels than the other extracts. -Glucosidase and acetylcholinesterase activities were inhibited by the cricket extracts in dichloromethane, similar to standard drugs. The crude extracts of the short-tailed cricket had the same anti-tyrosinase ability as kojic acid. These extracts showed no cytotoxicity in mouse subcutaneous connective tissue and human keratinocyte immortal cells. The GC-MS analysis confirmed that the inhibitory activity levels of the unsaturated and saturated fatty acids were the major components in the cricket extracts. Main finding: Cricket extracts from the domestic house cricket, field cricket and short-tailed cricket, displayed diverse potential as enzyme inhibitors for -glucosidase, -amylase, tyrosinase and acetylcholinesterase, supporting the future use of crickets as functional food ingredients.